Evaluating the Role of Instructional Leadership in Fostering Inclusive Education Practices within Primary Schools - Dedi Andrianto; Ilmi Suluki Rosyida; Mohamed Salah Elsayed Shalabi (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study evaluates the role of instructional leadership in fostering inclusive education practices within primary schools. The research investigates how principals, through their leadership practices, contribute to the development of a culture of inclusion, particularly for students with special needs. A mixed-method approach was employed, combining quantitative surveys of primary school teachers and qualitative interviews with principals and educators. The findings reveal that effective instructional leadership plays a crucial role in enhancing teacher engagement and promoting inclusive practices. Key leadership practices such as clear communication, ongoing support, and the active promotion of inclusivity were found to significantly impact the success of inclusive education. Additionally, the study highlights the importance of leadership training, with principals who received formal training being more capable of supporting inclusive practices. The involvement of the school community, including teachers, parents, and local stakeholders, was also identified as a critical factor in sustaining inclusive education practices. Finally, the study emphasizes the need for curriculum flexibility, showing that the ability to adapt teaching methods and materials to meet the diverse needs of students is vital for fostering inclusion. These findings underline the importance of comprehensive leadership development, community collaboration, and curriculum adaptability in creating inclusive primary school environments.